Peningkatan Kualitas Air Minum Bersumber dari Air Sumur Bor dengan Metode Filtrasi - Jumiati, Ety; Tambunan, Efrida Pima Sari (Navigation Physics : Journal of Physics Education, 2024)
Drinking water is a very important need for the body. Drinking water can be treated from borehole water sources which are not necessarily free from harmful chemical and microbiological substances such as pH and manganese. The aim of this research is to improve the quality of drinking water from Borehole water. The filter media used is treated natural zeolite type TNZ RC. 42, Activated carbon granular cartridge, and 1 and 3 µm Melt Blown Filter Cartridge. The testing parameter is chemical test (pH and Mn) and microbiology test (total coliform). The increment in pH levels from the research data were obtained sample A of 7,01, sample B of 7,08, sample C of 7,05 and sample D of 7,24, while the decrease in Mn levels from the research data were obtained sample A of 0,387 mg/L, sample B of 0,429 mg/L, sample C of 0,442 mg/L and sample D of 0,501 mg/L. In total coliform sample A, B, C and D of 0 CFU/100 mL, whose value may not exceed the maximum allowed standard of PERMENKES RI No.492/MENKES/PER/IV/2010.